PEMBINAAN KINERJA GURU OLEH KEPALA SEKOLAH UNTUK MENINGKATKAN MUTU PEMBELAJARAN PAI DI MA HIDAYATUL FAIZIEN - Mohammad Rif’at (CV. ADIBA AISHA AMIRA, 2025)
This thesis discusses the development of the performance of teachers by principals to improve the quality of learning PAI. The background of the problem is not optimal implementation guidance teacher performance by the principal, teacher competence weakness, lack of infrastructure facilities, has not been optimal management of information technology, and weak competitiveness, resulting in weakness of the quality of learning. The purpose of this study is to obtain an overview of Planning, Organizing, Implementation, Monitoring and assessment of performance coaching teacher by the principal to improve the quality of learning PAI. This study used a qualitative descriptive approach with case study method. Data collection techniques used observation, interviews and documentation. Results of this study summarized as follows: Planning begins with the consolidation of the principal by coaching participants (educators) and involves all aspects in schools through meetings and meetings; Organizing done by forming a management arrangement; Implementation by doing: fostering discipline, motivation, rewards and training; supervision is done by monitoring how the performance of teachers in schools and assessments carried out by assessing the performance of teachers whether in accordance with what is expected by the school or not. Suggestions from this study, among others, (1) The principal, should further enhance its role optimally and objectively by involving all the components and resources that exist in the school; (2) The PAI teachers should improve their competence and performance; (3) Disdik and MORA is expected to further enhance attention and assistance to schools in its territory; (4) The parents, should contribute to the school program and also support her son in collaboration with the school.